Implementation Of The Contrarius Actus Principle In Revocation Of Land Certificate Without A Court - Firman Freaddy Busroh; Fatria Khairo; Putri Difa Zhafirah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Proof of ownership of land is a land certificate. Often in the issuance of land certificates, there are problems. Land certificates that have been issued usually cause problems and must be canceled. One of the causes of the revocation of land certificates is invalid data which contains administrative defects. The problem arises that often the Head of the Land Office is reluctant to cancel the land certificate and prefers the applicant for the revocation of the land certificate to file a lawsuit in court or through litigation. This was suggested by the Head of the Land Office because of his misunderstanding of the Contrarius Actus principle. The Contrarius Actus principle is a principle in administrative law where the State Administrative Officer who makes State Administrative Decisions is automatically authorized to change, replace, revoke and cancel the documents he has made. and juridical defects must be revoked by the Head of the Land Office without having to wait for a court decision if they have fulfilled the revocation requirements.